Three Essentials for Making Effective Decisions - Kent Crookston (Academic Chairpersons Conference Proceedings, 2016)
In this workshop he shares three essential “ways-of-being” that govern all successful decisions: 1) be proactive, 2) be humble, and 3) be composed. Whether making group or individual decisions, whether following the classical process of multi-step deliberations or relying on one’s gut – alignment with these three essentials gives decision-makers confidence that their choices will be sensible and sustainable.
Keywords: three essential ways that govern all successful decisions